Health Care in the Caribbean and Central America - College of William and Mary, Williamsburg, VA. Dept. of Anthropology; McGlynn, Frank; College of William and Mary, Williamsburg, VA. Dept. of Anthropology ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
This publication examines a range of public health issues in the Caribbean Basin including conditions responsible for the transmission of disease, folk palliatives, and factors affecting preventive and curative health services on the national level. Comparisons are also made among the various Caribbean countries. The book has seven chapters: (1) "Health Systems Development in the English-Speaking Caribbean: Towards the 21st Century"; (2) "Sociocultural and Ecological Factors Influencing Schistosomiasis in St. Lucia"; (3) "Maternal-Child Health and Ganja in Jamaica"; (4) "Hypertension and Culture Change in the Caribbean"; (5) "The Crisis of the Dominican Republic Medical Model: Alternatives for the Year 2000" (6) "Health and Development in Central America"; and (7) "The Dilemma of Success: Revolutionary Achievements in Nicaraguan Health." (KWL)
Availability: Studies in Third World Societies, Department of Anthropology, College of William and Mary, Williamsburg, VA 23185.
Researchers.
Studies in Third World Societies, n30 Dec 1984.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cultural Influences; Developing Nations; Disease Control; Foreign Countries; Health Education; Health Needs; Health Personnel; Health Programs; Information Systems; Medical Services; Primary Health Care; Public Health; Caribbean -- Central America; Reports, Descriptive; Collected Works, Serials